2016
DOI: 10.1111/ecc.12553
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the executive function in breast cancer patients receiving chemotherapy treatment: a functional MRI study

Abstract: The aim of this study is to investigate chemotherapy-induced alterations in the functional framework of the brain, and probe the relationship between these changes and executive function impairments in breast cancer patients. Thirty-three breast cancer patients (BC) after receiving chemotherapy and 31 matched healthy controls (HC) were enrolled in this study. All participants received resting-state functional connectivity magnetic resonance imaging (rs-fcMRI) and neuropsychological background tests. The lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 55 publications
1
27
2
Order By: Relevance
“…The median PM2.5 in study homes was higher (33 μg/m 3 ) than seen in a multistate study of homes with woodstoves (17.5 μg/m 3 ) 27 and was higher than World Health Organization recommendations. 23 Elevated PM2.5 was associated with increased cough between colds in household children.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The median PM2.5 in study homes was higher (33 μg/m 3 ) than seen in a multistate study of homes with woodstoves (17.5 μg/m 3 ) 27 and was higher than World Health Organization recommendations. 23 Elevated PM2.5 was associated with increased cough between colds in household children.…”
Section: Discussioncontrasting
confidence: 67%
“…in respiratory symptoms 26. In addition, VOCs were present in all households, probably contributed by wood burning, tobacco smoke, fuel storage, and small engine repair in homes.The median PM2.5 in study homes was higher (33 μg/m 3 ) than seen in a multistate study of homes with woodstoves (17.5 μg/m 3 )27 and was higher than World Health Organization recommendations. In addition, VOCs were present in all households, probably contributed by wood burning, tobacco smoke, fuel storage, and small engine repair in homes.The median PM2.5 in study homes was higher (33 μg/m 3 ) than seen in a multistate study of homes with woodstoves (17.5 μg/m 3 )27 and was higher than World Health Organization recommendations.…”
contrasting
confidence: 67%
“…[25][26][27] By using fMRI, changes in brain activation have been observed during the execution of active tasks 25 as well as during rest (eg, in the attention and default mode network, a network that is involved in processes such as self-reflection, day dreaming, and rumination). [28][29][30][31][32] Interestingly, several recent reviews have demonstrated that practicing mindfulness meditation is associated with increased neural activation in brain regions related to external attention (ie, prefrontal and anterior cingulate cortex) [33][34][35][36] and reduced connectivity in the DMN involved in internal attention. 37,38 We hypothesized that an MBI would have an effect on resting state functional connectivity in networks related to both external attention and internal attention and would reduce both objectively and subjectively assessed cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that BC patients have brain structure changes after adjuvant chemotherapy, such as reduced gray matter and alterations in white matter. In addition, brain functional changes were observed in BC patients, such as decreased efficiency of functional connectivity (FC) and neural networks in a resting state ( Piccirillo et al, 2015 ; Tao et al, 2017 ), and cerebral activation alterations during the performance of cognitive tasks ( Silverman et al, 2007 ). Recently, researchers used resting-state FC to explore the neural activity of brain regions ( Fox and Raichle, 2007 ; Li et al, 2019 ; Liao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%